Microplastics: Classification, Sources, Characterisation, Fate, and Control Measures - Muniv, Yojana S.; Supanekar, Santosh P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Plastic use has now permeated all aspects of life and new applications are developed every year, and the substitution of other materials with plastic is still expanding in many sectors. They are currently used in single-use packaging, consumer goods, construction materials, automotive, electrical and agriculture applications. Several decades of plastic release into the environment have brought about a wide range of associated problems. Microplastics encompass a wide range of materials composed of different substances, with different densities, chemical compositions, shapes and sizes. They are ubiquitous in the environment and have been detected in a broad range of concentrations in marine water, wastewater, fresh water, food, air and drinking water, both bottled and tap water. Key sources of microplastic pollution are terrestrial run-off and wastewater effluent. Present paper deals with recent approaches on ‘microplastics’ with respect to: definition, common examples, classification, sources by usage sectors, key sources, characterisation, methods for analysis, fate in the aquatic environment, control measures, and research gaps is critically evaluated.